1992
DOI: 10.1063/1.463874
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional hydrogen tunneling dynamics in the ground vibrational state of the ammonia dimer

Abstract: We have measured and assigned more than 800 new far-infrared absorption lines and 12 new microwave absorption lines of the ammonia dimer. Our data are analyzed in combination with all previously measured far-infrared and microwave spectra for this cluster. The vibration-rotation-tunneling (VRT) states of the ammonia dimer connected by electricdipole-allowed transitions are separated into three groups that correspond to different combinations of monomer rotational states: A +A states (states formed from the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…Loeser et al 4 have shown that (NH 3 )z is nonrigid in many coordinates, including the umbrella mode V2 of NH 3 , and that a potential surface in all the soft degrees of freedom is probably required in order to contemplate executing the coupled large amplitUde vibrations that occur in the dimer. In this work only a highly restricted portion of configuration space is examined.…”
Section: Discussionmentioning
confidence: 98%
“…Loeser et al 4 have shown that (NH 3 )z is nonrigid in many coordinates, including the umbrella mode V2 of NH 3 , and that a potential surface in all the soft degrees of freedom is probably required in order to contemplate executing the coupled large amplitUde vibrations that occur in the dimer. In this work only a highly restricted portion of configuration space is examined.…”
Section: Discussionmentioning
confidence: 98%
“…A subsequent analysis by Loeser et al 5 of the farinfrared spectrum of the NH 3 dimer 5-7 revealed that the spectrum of the dimer is significantly more complex than initially suggested by the microwave study. Loeser et al 5 found, in fact, that the monomer inversion motion is not quenched in the dimer, thus requiring the use of the G 144 molecular symmetry group in the analysis.…”
Section: Introductionmentioning
confidence: 94%
“…VRT spectra of the A + E states, Loeser et al 4 observed transitions involving the K ) 2 state and included them in their analysis to achieve a good fit, so it is likely that the missing manifold here is likewise a K ) 2 manifold. Several approaches were attempted to treat these transitions.…”
Section: Methodsmentioning
confidence: 99%